Faktor-Faktor Yang Mempengaruhi Luas Pengungkapan CorporateSocial Responsibility (Studi Komparasi Bank Syariah dan Konvensional di Indonesia) - Alvianti, Galuh, Dra. Rina Trisnawati, Ak,Msi, Ph.D (2015)
Corporate Social Responsibility (CSR) is an issue that triggered the existence of a critical attitude from society regarding the global industry including the banking industry in Indonesia . Previous research on CSR in the banking industry have been done by Trisnawati et al ( 2011; 2012; 2013 ) and Fitria (2010 ). This study developed the research which conducted by Trisnawati , et al ( 2012) , Trisnawati , et al ( 2013 ) , Arifiyanto ( 2013) , Abdullah ( 2013 ) , and Ahzar ( 2013 . They examins CSR disclosure on conventional banks and Islamic banks in Indonesia. This study also developed the research by Nursiam and Gemitasari ( 2013 ) that focused on factors which have impact on CSR disclosure. The purpose of this study is to analyze CSR disclosure on conventional banks and Islamic banks in Indonesia and provide empirical evidence whether the variable firm size , leverage , board size , and composition of the board of commissioners influence on CSR in conventional banks and Islamic banks in Indonesia.The population in this study were all Banks listed in Indonesia Stock Exchange in 2011 - 2013, The sampling method is purposive sampling. The samples were 12 conventional banks and 8 Islamic banks. The technique performed statistical analysis by multiple linear regression and content analysis which using ISR and GRI convergence indicators with 90 items for conventional banks , and 105 items for Islamic banks (Trisnawati et al.2012 ) The analysis showed that CSR disclosure in conventional banks is higher than Islamic banks with the average score is 83.95 % , while the average CSR score is 78.85 % on Islamic bank. The results of multiple regression analysis showed that the size of the company and board size significantly affect the disclosure of CSR in conventional banks. While in Islamic banks only the firm size) was significantly effects on CSR. The research implication is the larger scale companies and had been intention by people would reveal their social responsibilities more completely.